A Study on CdCl2 Activation of CBD-CdS Thin Films - Kumarage, W.G.C.; Kumarasinghe, R.K.K.G.R.G; Wijesundera, R.P.; Jayalath, C.P.; Kaur, N.; Comin, E.; Dassanayake, B.S. (University of Jaffna, 2019)
“CdCl2 treatment” on CdTe absorber is known to be a key step for a drastic improvement of the CdS / CdTe solar cell conversion efficiency. However, CdCl2 treatment on the CdS window layer has not extensively studied in the literature. In this work, a detailed study is reported on CdCl2 solution treatment on chemical bath deposited of CdS (CBD-CdS). The CBD-CdS thin films were grown using 0.001 mol dm-3 CdSO4 (3CdSO4.8H2O, 99%, Sigma Aldrich, USA), 0.002 moldm-3 CS(NH2)2 (99%, Sigma Aldrich, USA) and 1.1 ml of NH4OH (NH3, 35% w/w, Sigma Aldrich, USA) at a bath temperature of 80 °C for one hour on FTO glass substrates (~10 Ω /□, TEC 10, Sigma-Aldrich, USA). For the CdCl2 treatment, deposited CBD-CdS thin films were dip-coated in a saturated methanol (99.8%, ACS reagent, Sigma Aldrich, USA) solution of CdCl2 (99%, Fluka, USA). Later the CdCl2 treated samples were cleaned with DI water and annealed at 200 °C for one hour. The dipping duration was varied from 0 to 20 minutes. The CdCl2 treatment was found to increase the cluster size of CdS thin films and the formation of clusters was identified to be due to coalescence of small clusters. Higher VOC and ISC parameters in the photoelectrochemical cell (CdS/0.1 M Na2S2O3/Pt) were observed for CdCl2 treated CBD-CdS thin films, compared to untreated CBD-CdS thin films. The improved, VOC and ISC parameters found may be due to high effective area as well as grain boundary passivation. The flat band potential (Vfb) value was found to be tunable with CdCl2 treatment duration. The photo efficiency was found to be almost doubled for CdS films which underwent CdCl2 treatment for 10 minutes, compared to the untreated ones
Keywords: CBD; CdS; CdCl2; activation